Reduced Serum Phosphorus Levels Were Associated with Metabolic Syndrome in Men But Not in Women: A Cross-Sectional Study among the Japanese Population - Shimodaira, Masanori; Okaniwa, Shinji; Nakayama, Tomohiro (Annals of nutrition and metabolism, 2017)
Reduced serum phosphorus (SP) levels are reported to be associated with insulin resistance and metabolic syndrome (MetS). However, there have been a few gender-specific studies although SP levels are substantially different between men and women. This is a cross-sectional study. A total of 16,041 subjects (9,076 men and 6,965 women) were analyzed. The subjects were divided into 3 groups of gender-specific tertiles based on phosphorus levels: the lowest (T1), middle (T2), and the highest (T3). SP levels were significantly lower in subjects with MetS than in those without MetS in men but not in women. Waist circumference and fasting plasma glucose were negatively and high-density lipoprotein cholesterol was positively correlated with SP levels both in men and women. Blood pressure (BP) and triglycerides (TG) were negatively correlated with SP levels in men, while they were positively correlated with SP levels in women. Lower SP levels were associated with the prevalence of MetS in men (T1; 19.9%, T2; 16.9%, and T3; 14.3%; p < 0.001) but not in women (T1; 14.1%, T2; 16.6%, and T3; 15.3%; p = 0.282). BP and TG were unexpectedly positively correlated with SP levels in women. Reduced SP levels were associated with MetS in men but not in women.